Virulotyping and Antibiograms of Pathogenic Escherichia coli Isolated from Calves Suffering from Diarrhea - El refaey, Mona; Elkenany, Rasha; Younis, Gamal (Journal of Advanced Veterinary Research, 2023)
Escherichia coli is an important cause of diarrhea in calves and has negative economic effects on the livestock industry worldwide due to high mortality and reduced growth rate. The present study was aimed to investigate the prevalence of E. coli in 120 fecal samples from diarrheic mixed-sex neonatal calves, molecular detection of virulence genes, and antimicrobial resistance testing. The high occurrence of E. coli (90/120; 75%) was detected in diarrheic calves. The molecular detection of virulence genes (iron, papc, asta, iuta, omp, hyl and iuc) showed that the high occurrence of astA (78.8%), iucD (66.6%), and papC (64.4%) genes in examined strains, while only 19 strains devoid of virulence genes. Furthermore, antimicrobial susceptibility testing of E. coli isolates showed absolute resistance to ampicillin (100%), followed by streptomycin (95.5%), tetracycline, sulfonamides, gentamycin and chloramphenicol (77.7% each). In the other hand, strains revealed high rates of susceptibility to ciprofloxacin (80%) and enrofloxacin (77.8%).Â  The multidrug-resistant (MDR) E. coli strains were determined as 77.7% (70/90) and the most identified antimicrobial resistance patterns in 31 strains was C, S, CN, N, TET, AM, SXT. Also, the identified antibiotypes had MAR index values ranged from 0.1 to 0.9. The results of current study indicate the importance of routine monitoring of E. coli isolated from diarrhetic calves to reduce the transmission to humans and animals as well as to select the most appropriate antibiotics. The antibiograms in our study emphasizes the risks associated with the random use of antibiotics. Â 